Nutritional assessment - Lee, Robert D. 1952-; Nieman, David C. 1950- (McGraw-Hill, 2013)
"This text describes the four major methods of nutritional assessment (dietary, anthropometric, biometric, and clinical) in an understandable and contemporary way. It thoroughly covers assessment of the hospitalized individual, but also serves as an invaluable resource to the nutrition professional working in such areas as public health and community nutrition, corporate health, and sports medicine"-- Provided by publisher.